Pollution assessment of potentially toxic elements in marine sediment from Puerto Princesa Bay, Palawan, the Philippines - Bautista, Charles Paul A.; Punzalan, Jervee M.; Samaniego, Jessie O.; Gibaga, Cris Reven L.; Tanciongco, Alexandria M.; Quierrez, Rico Neil M.; Gervasio, Gregorio C.; Rachelle Clien G. Reyes (2024)
The enrichment levels of potentially toxic elements (PTEs) have recently attracted global concerns due to their associated environmental risks and threats to human health. This study, therefore, aims to assess the pollution impacts of these PTEs from 53 marine sediment samples from Puerto Princesa Bay, Palawan, the Philippines. The concentrations of eight PTEs (As, Co, Cr, Cu, Hg, Mn, Ni, and Zn) were determined using portable X-ray fluorescence spectroscopy and direct mercury analyzer. Spatial distribution maps of the bay revealed similar trends for Cr, Co, Cu, Mn, Ni, As, and Zn, with higher concentrations found at the north-western side of Puerto Princesa Bay. Factor analysis revealed that this trend can be attributed to natural provenance. Moreover, a higher concentration of As was concentrated in the southern part of the bay adjacent to the built-up areas of Puerto Princesa City, whereas Hg had higher concentrations in the northern part. Their distribution can be attributed to anthropogenic influence: Hg transport exacerbated by historical mercury mining upstream and industrial activities in the built-up bay that lead to the enrichment of As. Further assessment using the enrichment factor and index of geoaccumulation indices support the mentioned factors of PTEs based on their enrichment and contamination levels. Lastly, the total potential ecological risk index revealed Co, Hg, and Ni – which are most likely to be the main pollutants – particularly in the northern part of the bay. Based on the evaluated indices, these PTEs are potential sources of ecological risks to the environment, as well as to the inhabitants of the area. The results are significant inputs in baselining the current PTE pollution caused in Puerto Princesa Bay, Palawan, as well as for decisions regarding mixed-use planning of the bay area.
Keywords: Marine sediments; Marine pollution